Relative Assessment of Biochemical Constituents and Antioxidant Potential of Fermented Wheat Grains Using Bacillus subtilis KCTC 13241 - Muhammad Zahaib Ilyas; Ju Kyong Lee; Muhammad Waqas Ali; Sana Tariq; Muhammad Nadeem (Fermentation, 2022)
High antioxidant levels in food are gradually becoming popular because of enhanced risk of oxidative stress in humans. Bread wheat is rich in vital antioxidants, but a major portion of its bioactive compounds are not available to humans. This study was conducted with the aim to fulfill the antioxidants and nutrients gap between the available and potential levels of wheat grains through fermentation by Bacillus subtilis KCTC 13241. In this experiment, the whole wheat grains were used by keeping in consideration the importance of minerals and to measure an increase in their availability after fermentation. The antioxidants and nutritional potential of different wheat varieties was determined by DPPH (2,2-diphenyl-1-picryl- hydrazyl) and ABTS (3-ethyl-benzothiazo- line-6-sulfonic acid) radical scavenging assays as well as by the concentration of amino acids, flavonoids, minerals, carbohydrates and phenolic compounds. Different wheat varieties were showed different free radical scavenging potential after fermentation, which was significantly higher with respect to their corresponding unfermented wheat varieties. The highest nutritional and free radical scavenging potential was found in a fermented wheat variety, named Namhae, and this combination is highly useful for cereal-based food industries.